Pyoderma gangrenosum and ulcerative colitis in the tropics - Alese,Olatunji B. (2008)
Pyoderma gangrenosum is a rare inflammatory skin condition, characterized by progressive and recurrent skin ulceration. There may be rapidly enlarging, painful ulcers with undermined edges and a necrotic, hemorrhagic base. Disorders classically associated with pyoderma gangrenosum include rheumatoid arthritis, inflammatory bowel disease, paraproteinemia and myeloproliferative disorders. There have been some reports of the occurrence of pyoderma gangrenosum in Africa, and in Nigeria, but only one specifically reported pyoderma gangrenosum in association with ulcerative colitis. We report on a 45-year-old man who presented with pyoderma gangrenosum associated with ulcerative colitis; the second report in Nigeria. The skin lesions were managed with daily honey wound dressings. Oral dapsone and prednisolone were started. The frequency of the bloody diarrhea decreased, and was completely resolved by the second week after admission. The ulcers also showed accelerated healing. The goal of therapy is directed towards the associated systemic disorder, if present.